Hubungan Penggunaan Online Food Delivery, Emotional Eating, dan Kualitas Diet dengan Status Gizi Lebih: Associations of Online Food Delivery Use, Emotional Eating, and Diet Quality with Overweight and Obesity - Wijasukmaya, Nazwa Rahma; Insani, Hurry Mega; Santanu, Ayu Mutiara; Astuti, Widya (Jurnal Ilmu Gizi dan Dietetik, 2026)
Overweight and obesity are global health issues that continue to rise in the modern era, including in Indonesia. The increasing use of online food delivery (OFD) services, which often promote unhealthy food choices, along with high levels of emotional eating and poor dietary quality, are believed to contribute to the growing prevalence of overweight and obesity, particularly among university students. The objective of this study is to describe the prevalence of overweight and obesity and to examine their associations with the frequency of online food delivery (OFD) orders, OFD ordering practices, emotional eating, and diet quality among students at Universitas Pendidikan Indonesia. A cross-sectional design was employed in this study, involving 80 undergraduate participants selected through proportional stratified random sampling. Data were gathered through validated questionnaires and direct anthropometric measurements. The Chi-square test and Odds Ratio (OR) were used for analysis. The results showed that 54.4% of students rarely used OFD services, 51.9% had poor OFD ordering practices, 53.2% exhibited high levels of emotional eating, 54.4% had poor diet quality, and 32.9% were classified as being overweight or obesity. Emotional eating (p=0.003; OR=4.7) and poor diet quality (p<0.001; OR=5.9) were significantly associated with overweight and obesity. Neither the frequency nor the practice of OFD usage was significantly associated with being overweight or obesity (p>0.05). Students with high emotional eating and poor dietary quality were more likely to experience overnutrition.